Effect of thermal cycling on microtensile bond strengths of various adhesives to dentin - Gulsah Akin; Ozden Ozel-bektas; Seyda Herguner-siso (Cumhuriyet University, 2011)
Objectives: The objective of this study was to evaluate the effect of thermal cycling on microtensile bond strengths (MTBS) of various adhesives to dentin. Methods: Three adhesive systems including a 1-step self-etch adhesive system (G-Bond), a 2-step self-etch adhesive system (AdheSE), and an etch&rinse adhesive system (Prime & Bond NT) were evaluated. Twenty-four extracted molars were used. After grinding the coronal enamel surface, the teeth were randomly divided into 6 groups (n=4) (G-Bond, G-Bond+thermal cycling, AdheSE, AdheSE+thermal cycling, Prime & Bond NT, and Prime & Bond NT+thermal cycling). Adhesives were applied according to each manufacturer's instructions followed by resin composite polymerization. Groups without thermal cycling were stored in distilled water at 37 0C for 24 hours and used for immediate testing of the MTBS. Groups with thermal cycling were subjected to thermocycling (10.000 cycles between 5 0C and 55 0C, for a dwell time of 30 seconds). For MTBS test, teeth were sectioned occluso-gingivally into a serial slabs and further sectioned into composite-dentin sticks. Testing was performed on a universal testing machine at a crosshead speed of 1.0 mm/min. One-way ANOVA and post hoc Tukey-Kramer multiple comparisons tests (α=0.05) were performed on all data. Results: The results of the MTBS test showed that the highest bond strengths were observed in etch&rinse adhesive groups (3 and 3T). A statistically significant difference in MTBS was found between group 1 and group 1T (p